Hemoglobin mass and biological passport for the detection of autologous blood doping - Pottgiesser, T.; Echteler, T.; Sottas, P.-E.; Umhau, M.; Schumacher, Y. O. (Medicine & Science in Sports & Exercise, 2012)
Purpose: The most promising attempt to reveal otherwise undetectable autologous blood doping is the Athlete Biological Passport enabling a longitudinal monitoring of hematological measures. Recently, the determination of hemoglobin mass (tHb) was suggested to be incorporated in the adaptive model of the Athlete Biological Passport. The purpose therefore was to evaluate the performance of tHb as part of the adaptive model for the detection of autologous blood transfusions in a longitudinal blinded study. Methods: Twenty-one subjects were divided into a doped group (n = 11) and a control group (n = 10). During the time course of a simulated cycling season (42 wk) including three major competitions (Classics, Grand Tour, World Championships), multiple autologous transfusions of erythrocyte concentrates were assigned in the doped group. A blinded investigator ordered up to 10 tHb measurements (carbon monoxide rebreathing) per subject, mimicking an intelligent doping testing approach in obtaining hematological data (tHb, OFFmass (novel marker including reticulocytes), and respective sequences) for the adaptive model. Results: The final analysis included 199 of 206 overall tHb measurements. The use of tHb, OFFmass, and their sequences as markers of the adaptive model at the 99% specificity level allowed identification of 10 of 11 doped subjects (91% sensitivity) including one false positive in the control group. At the 99.9% specificity level, 8 of 11 subjects were identified without false positives (73% sensitivity). Conclusions: It seems that the problems of tHb determination by carbon monoxide rebreathing limit the application of this method in antidoping. Because of its potential to detect individual abnormalities associated with autologous blood transfusions shown in this study, a method for tHb determination that is compatible with today's standards of testing should be the focus of future research.